2017
DOI: 10.3389/fnhum.2017.00209
|View full text |Cite
|
Sign up to set email alerts
|

Pupillary Response to Negative Emotional Stimuli Is Differentially Affected in Meditation Practitioners

Abstract: Clinically, meditative practices have become increasingly relevant, decreasing anxiety in patients and increasing antibody production. However, few studies have examined the physiological correlates, or effects of the incorporation of meditative practices. Because pupillary reactivity is a marker for autonomic changes and emotional processing, we hypothesized that the pupillary responses of mindfulness meditation practitioners (MP) and subjects without such practices (non-meditators (NM)) differ, reflecting di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…The former two studies find that the pupils generally dilate more to positive and negative stimuli compared to neutral stimuli. In contrast Franzen et al (2009) and Vasquez-Rosati et al (2017) show greater pupil dilation to negative images as compared with neutral and positive images. Translating this line of research onto predictors of alcohol relapse will also have to consider the inter-individual variability in the assessment of alcohol as negative or positive.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The former two studies find that the pupils generally dilate more to positive and negative stimuli compared to neutral stimuli. In contrast Franzen et al (2009) and Vasquez-Rosati et al (2017) show greater pupil dilation to negative images as compared with neutral and positive images. Translating this line of research onto predictors of alcohol relapse will also have to consider the inter-individual variability in the assessment of alcohol as negative or positive.…”
Section: Discussionmentioning
confidence: 83%
“…Further testing with positive and negatively emotionally valenced stimuli, non-alcohol beverages or in the context of stress-induced craving are required to dissociate emotional valence from arousal effects (Pulido et al 2010). Previous studies have investigated pupillary dilations and contractions to emotional images of neutral, positive, and negative emotional valence (Bradley et al 2008; Franzen et al 2009; Dietz et al 2011; Vasquez-Rosati et al 2017). The former two studies find that the pupils generally dilate more to positive and negative stimuli compared to neutral stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroinflammation has been shown previously to be increased in Tg Tau P301S mice (51,69) and is likely to exacerbate the neurodegeneration and Tau pathology (69). We carefully investigated the impact of chronic SYK inhibition on neuroinflammation in Tg Tau P301S mice by analyzing the levels of various pro-inflammatory cytokines and by quantifying Iba-1 and iNOS levels as markers of microgliosis (70,71), as well as GFAP to measure astrogliosis (72). We found that Iba-1, iNOS, and various pro-inflammatory cytokine levels were markedly increased in Tg Tau P301S mice compared with WT littermates, whereas GFAP levels were unchanged.…”
Section: Spleen Tyrosine Kinase Blocks Autophagic Tau Degradationmentioning
confidence: 99%
“…Evidence from the field of cognitive neuroscience suggests that long-term involvement in meditation decreases the reaction intensity of the autonomic nervous system [ 76 ] and may also increase cognitive flexibility [ 77 ] and produce positive effects on emotion-cognition interactions [ 75 ]. Zen is advocated by the writers as a spiritual path that leads to healing in the personal, social, and ecological dimensions [ 73 ].…”
Section: Discourse Of a Systemic Resiliencementioning
confidence: 99%